157 Non-Surgical Management of an Acute Isolated Volar Dislocation of the Distal Radio-Ulnar Joint. (12th October 2021) - Sreenivasan, S; Nair, R; Das, D; Talawadekar, G
Abstract: Isolated distal radio-ulnar joint dislocations are rare and commonly missed on radiographs. A young male presented with severe pain and deformity of the left wrist, following a collision whilst playing rugby. This was easily diagnosed using plain radiographs, and the initial attempted reduction methods in the Emergency Department failed. The patient was subsequently anaesthetised in theatre, yet reduction by an accepted method of palmar to dorsal pressure over the interosseous membrane with simultaneous distraction of the wrist failed. A further attempt to manipulate the dislocated ulnar head was successful, with the same force applied whilst the wrist was maximally flexed and pronated – thereby avoiding an open reduction. The patient was asymptomatic at final follow-up, over one year later. This technique has not previously been described in the literature and may be used in similar injuries in the future.